THE EFFECT OF ORGANIZATIONAL CULTURE AND WORK DISCIPLINE ON JOB SATISFACTION OF BIMA CITY SOCIAL SERVICE EMPLOYEES - Syarifudin Syarifudin; Jaenab Jaenab (Universitas Putera Batam, 2021)
This study aims to explain the influence between organizational culture and work discipline variables on employee job satisfaction simultaneously and partially. This type of research is associative research with a quantitative approach. The population in this study were 56 employees and the research sample used was using the slovin formula, namely 36 employees at the Bima City Social Service. The analysis used is multiple linear regression. The results of the study simultaneously show that organizational culture and work discipline have a significant effect on employee job satisfaction. sig value. F obtained is 0.000. The results of the study partially show that organizational culture has a significant effect on employee job satisfaction with a sig. t is 2,626. The results of the study partially show that organizational culture and work discipline have a significant effect on employee job satisfaction with a sig.t value of 4.825.